ExoMars PanCam Field Test Report from the Arctic Mars Analogue Svalbard Expedition (AMASE) 2008 - Schmitz, N.; Barnes, D.; Coates, A.; Griffiths, A.; Hauber, E.; Jaumann, R.; Michaelis, H.; Paar, G.; Trauthan, F.; AMASE 08 Crew (ESA, 2008)
From 4-17 August 2008, the 6th Arctic Mars Analogue Svalbard Expedition (AMASE) 2008 will take place in the Svalbard archipelago, Norway, which is considered to be an excellent analogue site for early Mars. An international crew of scientists and engineers involved in Mars exploration will study the geology, geophysics, biosignatures, and life forms that can be found in the volcanic complexes, warm springs, subsurface ice, and sedimentary deposits of Svalbard by using instruments, a rover (NASA's CliffBot), and techniques that will/may be used in future planetary missions, such as NASA's Mars Science Laboratory (MSL) or ESA's ExoMars. For general performance testing in a representative environment prior to the ExoMars Payload Design Review and to investigate how the instruments can be best used to plan the first part of the ExoMars science strategy, ESA together with the Earth and Planetary Exploration Services (EPX) and the Carnegie Institution of Washington (CIW) invited Pasteur Payload instrument teams to join the AMASE 2008 campaign. The PanCam, WISDOM, MIMA, and Raman-LIBS teams were finally selected to take part. Here, we report on AMASE 08 field test results of the Panoramic Camera system. PanCam is being developed as part of the Pasteur Exobiology Payload of the ExoMars rover. The ExoMars PanCam instrument will consist of two wide-angle cameras (WACs), which are to provide multispectral stereo images with 34° field-of-view (FOV) and a High-Resolution Channel (HRC) to provide monoscopic 'zoom' images with 5° field-of-view. Accordingly, the instrument to be used during AMASE 2008 will consist of two consumer wide angle cameras (1024x768 CCD, 33.4° FOV) and a breadboard of the ExoMars PanCam HRC (1024x1024 APS, 5° FOV, focus mechanism) mounted on a tripod. This setup will be used to perform multi-spectral geological imaging, colour and stereo panoramic and high-resolution imaging (as planned for ExoMars) in a Mars relevant context under very realistic conditions using realistic targets. Beyond demonstrating ...